Jude the Obscure de Thomas Hardy et l’autorité de la lettre - Stéphanie Bernard (Revue LISA)
Thomas Hardy is usually considered a Victorian writer. Nonetheless, his last novel Jude the Obscure, announced the era of modernity which started with the twentieth century, just before he abandoned fiction to concentrate on poetry. With modernity looming in the background, Jude the Obscure allowed for the rewriting of tragedy. Urban settings have replaced the countryside and all signs of transcendence have vanished from society. This defeat of the divine is nevertheless accompanied by a great number of biblical references. Thomas Hardy quotes and uses the Divine Letter as if to rewrite it rather than to appear faithful to the Word. The text keeps offering itself to the spell of voice: it does so when Job utters words of revolt and then worship, when Jude lets his imagination flow from his lips so that he seems to live on in the text after he is dead, or when the voice of the novelist becomes the voice of a poet.